Let $f_*:C_*\to D_*$ be a chain map. I'm stuck in the proof of the following statement:

$f_*$ induces an isomorphism in homology iff the mapping cone of $f_*$, cone($f_*$), is contractible.

(For information about the mapping cone of a chain map see for example here https://ncatlab.org/nlab/show/mapping+cone , definition 6 and proposition 6).

Proof: Consider the short exact sequence of chain complexes $$0\to D_*\to \operatorname{cone}(f_*)\to \Sigma C_*\to 0, $$where $i_*D_*\to \operatorname{cone}(f_*)$ is the inclusion and $p_*:\operatorname{cone}(f_*)\to \Sigma C_*$ is the projection onto the suspension of $C_*$. Then there is a long exact sequence in singular homology

$$..\to H_n(D_*)\to H_n(\operatorname{cone}(f_*))\to H_n(\Sigma C_*)\xrightarrow{\partial_n} H_{n-1}(D_*)\to ..,$$furthermore it is $H_n(\Sigma C_*)\cong H_{n-1}( C_*)$. Now I'm stuck to prove that $\partial_n$ as a map $H_{n-1}( C_*)\to H_{n-1}( D_*)$ equals $H_{n-1}(f_*):H_{n-1}( C_*)\to H_{n-1}( D_*)$. I considered the explicit contruction of $\partial_*$ in the snake lemma, nevertheless I wasn't able to prove this. Can we elaborate it?

The next steps are: We have the long exact sequence $$..\to H_n(D_*)\xrightarrow{H_n(i_*)} H_n(\operatorname{cone}(f_*))\xrightarrow{H_n(p_*)} H_{n-1}( C_*)\xrightarrow{H_{n-1}(f_*)} H_{n-1}(D_*)\xrightarrow{H_{n-1}(i_*)} H_{n-1}(\operatorname{cone}(f_*))\to ..$$

$"\Leftarrow "$: If $\operatorname{cone}(f_*)$ is contractible, then $H_n(\operatorname{cone}(f_*))=0$ for all $n\in\mathbb{N}$. The sequence in homology is exact, it follows that $H_n(f_*)$ is an isomorphism for all $n\in\mathbb{N}$.

$"\Rightarrow "$: For fixed, but arbitrary $n\in\mathbb{N}$ the map $H_n(f_*)$ is an isomorphism. It follows: $\operatorname{ker}(H_{n+1}(p_*))=H_{n+1}(\operatorname{cone}(f_*))$ and $\operatorname{im}(H_{n+1}(i_*))=0$ ( because $H_{n+1}(f_*)$ is an isomorphism). But otherwise it is $\operatorname{im}(H_{n+1}(i_*))=\operatorname{ker}(H_{n+1}(p_*))$, i.e.: $H_{n+1}(\operatorname{cone}(f_*))=0$ and $H_{0}(\operatorname{cone}(f_*))=0$. It follows that $\operatorname{cone}(f_*)$ is contractible.

So the only thing which is not clear for me is that $\partial_n:H_{n-1}( C_*)\to H_{n-1}( D_*)$ equals $H_{n-1}(f_*):H_{n-1}( C_*)\to H_{n-1}( D_*)$. I appreciate your help.



It's probably far easier (and instructive) to prove the fact directly. (Moreover it's possible for a chain complex to have vanishing homology but not be contractible, consider the chain complex $$\dots \to 0 \to \mathbb{Z} \xrightarrow{2 \cdot} \mathbb{Z} \to \mathbb{Z}/2\mathbb{Z} \to 0$$ but the correct statement is indeed that $f_*$ is an isomorphism in homology iff the mapping cone has vanishing homology groups).

Recall that the mapping cone $Z_*$ is given by $Z_n = D_n \oplus C_{n-1}$ and $$d_Z(y,x) = (d_D(y) + f(x), -d_C(x)).$$

$(\implies)$ Suppose that $f_*$ is an isomorphism in homology. Let $[z] \in H_n(Z)$ be some homology class, represented by a cycle $z \in Z_n$. We want to show that $[z] = 0$, i.e. that $z$ is a boundary.

Write $z = (y,x) \in D_n \oplus X_{n-1}$. We know that $z$ is a cycle, i.e. $$d_Z(z) = 0 = (d(y) + f(x), -d(x)) \implies d(x) = 0 \text{ and } f(x) = d(-y).$$ Thus $x \in X_{n-1}$ is a cycle, and so we can consider $[x] \in H_{n-1}(C)$. But $f(x) = d(-y)$ means that $f(x)$ is a boundary, i.e. $f_*[x] = 0$. Since $f_*$ is an isomorphism, hence injective, and $[x] = 0$ too. So $x = d(x')$ is a boundary for some $x' \in C_n$ (Fact 1).

But now $0 = d(y) + f(x) = d(y) + f(d(x')) = d(y + f(x'))$, and so $y + f(x') \in D_n$ is a cycle, $[y + f(x')] \in H_n(D)$. But $f_*$ is an isomorphism, hence surjective, and thus $[y+f(x')] = f_*[x'']$ for some cycle $x'' \in C_n$, hence $y = f(x''-x')$ (Fact 2).

Combining the two facts, we get: $$d(0,x''-x') = (f(x''-x'), -d(x''-x') = (y,x) = z$$ as we wanted.

$(\impliedby)$ Now suppose that all the homology groups of the mapping cone vanish, i.e. $H_*(Z) = 0$. We want to show that $f_*$ is an isomorphism in homology.

  • $f_*$ is injective: Let $[x] \in H_n(C)$ be such that $f_*[x] = 0$, i.e. $dx = 0$ and $f(x) = dy$ for some $y \in D_{n+1}$. We want to show $[x] = 0$. But then $(y,-x) \in Z_{n+1}$ is a cycle: $d(y,-x) = (dy - f(x), -dx) = 0$. Since $H_{n+1}(Z) = 0$, it follows that $(y,-x)$ is a boundary, $(y,-x) = d(y',x') = (dy' + f(x'), -dx')$. In particular $x = dx'$ is a boundary, hence $[x] = 0$ as we wanted.

  • $f_*$ is surjective: let $[y] \in H_n(D)$ be represented by a cycle $y \in D_n$ ($dy = 0$). Then $(y,0) \in Z_n$ is a cycle, so it's a boundary (because $H_n(Z) = 0$): $(y,0) = d(y',x') = (d(y') + f(x'), -dx')$. So $x' \in C_n$ is a cycle, and $[y] = [d(y') + f(x')] = [f(x')] = f_*[x']$ is in the image of $f_* as we wanted.

I know it looks like a lot of words, but the underlying reasoning is not very complex. It's a simple diagram chase, and it mostly boils down to keeping track of all the definitions and hypotheses correctly. There's only one thing to do at each step, and so we do it (and the mapping cone is designed precisely so that everything works out).

  • 3
    $\begingroup$ thank you very much, it's very very helpful! You wrote down the proof very understandable and detailed. thanks a lot! $\endgroup$ – alg Feb 10 '16 at 6:47
  • 1
    $\begingroup$ @Watson I think you're right, I hope it's correct now (I'm terrible with signs). $\endgroup$ – Najib Idrissi May 28 '16 at 15:58
  • $\begingroup$ @NajibIdrissi You're of course right in noting that the statement should be about acyclicity instead of contractibility, but your example is not correct - the chain complex there is indeed contractible. $\endgroup$ – Hanno May 28 '16 at 16:03
  • $\begingroup$ @Hanno It should be correct now. Better late than never :) $\endgroup$ – Najib Idrissi Feb 28 '18 at 11:44
  • 1
    $\begingroup$ @Driver8 The proof should go as follows. The assumption implies $y = f(x''-x') + d(y')$ for some $y'\in D_{n+1}$. Then $d(y', x''-x') = (d(y')+f(x''-x'), -d(x''-x')) = (y, d(x')) = (y,x)$, where we use that $x''$ is a cycle, that is $d(x'')=0$. $\endgroup$ – Vincent Boelens Jul 27 '18 at 12:08

To see the connecting morphism in the LES involving the cone of a map $f: C\to D$ is $Hf$, you follow the definition of the connecting morphism: the SES is $D\to \text{cone}(f) \to C$ where one map is the inclusion and the other is the projection. The boundary of a cycle $c\in C$ is computed as follows: lift $c$ to $\text{cone}(f)$, which can be done since the projection is onto, then take the differential of this, and the class of this is $\partial c$.

Now suppose $c\in C$ is a cycle. You can always lift this to the cone by $(0,c)$, and then apply the differential of the cone to $(0,c)$, which gives $(fc,0)$ since $dc=0$. This element naturally comes from $fc\in D$, so the class of this is $\partial c$. Thus $Hf$ is the boundary of the LES.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.